STRATEGIES ON COPING STRESS AMONG FILIPINO EMPLOYEES IN THE PRIVATE SERVICE INSTITUTIONS IN THE KINGDOM OF BAHRAIN - Salamat Guansi, Dr. Steve; Jasim Shaker, Mr. Redha; *, Manama (IJRDO - Journal of Business Management, 2017)
The study entitled “Strategies on Coping Stress among Filipino Employees in the Private Service Institutions in the Kingdom of Bahrain” has considered three specific problems and it dealt with the frequency of the causes of stress among Filipino Employees, the seriousness of the effects of stress to employees and the strategies on coping up with stress at work. Specifically, the research included one hundred respondents – fifty (50) males and fifty (50) female employees who are connected with various service institutions operating in the Kingdom of Bahrain. Survey – questionnaires were floated to respondents, data were gathered and collected and were interpreted using statistical tools that include descriptive and inferential statistics. In the study, the problem that included the following indicators such as disruptive behavior of customers, unbecoming behavior of heads, conflicts with colleagues, workload and time pressures, role conflict and ambiguity, working environment and inadequate resources were all perceived by both male and female employees as Frequent (F). This has measured the frequency of the causes of stress among Filipino Employees in the Private Service Institutions in the Kingdom of Bahrain. On the degree of seriousness of the effects of stress to employees dealing with work in the Private Service Institutions in the Kingdom of Bahrain, the indicators such as Physiological Effects (fatigue and illness); Psychological Effects (job dissatisfaction, anxiety and decrease in productivity); and Behavioral Effects (inability to manage time or delegate, feelings of alienation and inadequacy, loss of confidence and motivation, irritability with colleagues/unwillingness to cooperate and persistent negative thoughts) were both perceived by male and female Filipino Employees in the Kingdom as Serious (S). Rated by all respondents as Applicable (A), the following were noted as strategies on coping stress at work among Filipino Employees in the Private Service Institutions in the Kingdom of Bahrain such as physical exercise and relaxation practices, recreation and leisure time activities, diet and sleep, time management, behavioral self – control, networking, organizational intervention, minimizing frequency and intensity of stressful situation and social support